REDEFINING CULTURAL DIMENSIONS: THE LIVED EXPERIENCES OF INDONESIAN INTERNATIONAL STUDENTS IN ASIA - Fernando, Joshua; Supiyandi, Andi; Sulistiawati, Asri; Apriza, Dwi Kartini (ASPIRATION Journal, 2024)
Many Indonesian Diaspora are studying as international students at various universities worldwide. Cross-cultural communication plays a vital role in actualizing Indonesian students, especially in interacting with local residents. This study aims to determine the pattern of cross-cultural interaction and understand the six cultural dimensions in the Asian continent through the perspective of the Indonesian Diaspora, namely Indonesian students abroad. This research examines the construction of meaning that occurs using research instruments in the form of in-depth interviews and documentation studies in the perspective of Hofstede's Cultural Dimension Theory. This research is based on the cross-cultural communication paradigm, namely dialectics as an integration between functionalist and critical paradigms with a descriptive qualitative research approach. The study results indicate a discrepancy between Hofstede's functional data and the social reality experienced by diaspora students. Several cultural dimensions, such as power distance, individualism vs collectivism, and indulgence vs restraint, experience reinterpretation in everyday social practices. Communities with low individualism scores tend to be closed to foreigners, while collectivist societies show openness and responsiveness to newcomers. These findings confirm that cultural dimensions are contextual and dynamic and are greatly influenced by the negotiation of meaning in intercultural social interactions. Thus, this study enriches the understanding of cultural flexibility and the importance of a micro approach in reading cross-cultural communication in international education.